ASSESSING AND EVALUATING EFL LEARNERS’ ABILITY IN WRITING ACADEMIC ESSAY - M. Fadhly Farhy Abbas (Universitas Negeri Padang, 2017)
English as Foreign Language (EFL) learners in Indonesia, especially in English Education Department is strongly expected to have good writing skill. This is because the learners’ achievement in writing can be used as a valuable contribution towards the development of English Language Teaching (ELT) in Indonesia, especially in the teaching of writing skill. Therefore, it needs a writing assessment and evaluation to measure the learners’ writing skill. This study aims at assessing and evaluating the EFL learners’ ability in writing an essay, especially in writing academic or scientific essay. Quantitative method with descriptive quantitative design employed in this study. The writing test and unstructured interview were used in this study as research instrument. This study was conducted on November 2016 at University of Lancang Kuning, Indonesia. There were 80 learners selected as participants in this study. The result of the writing test showed that the learners’ average score was 68.8 and it was categorized into fair level. Moreover, based on the interview the learners said that they felt difficult in developing and organizing idea with correct grammar and diction in a composition. It was basically influenced by limited writing strategy and learning materials. Therefore, appropriate learning materials supported by writing strategy are needed to facilitate and improve the learners’ writing skill. In conclusion, the learners’ writing skill is in fair level of ability.